Exchange Rate and Foreign Reserves Interface: Empirical Evidence from Nigeria - Kalu, Ebere Ume; Ugwu, Ogochukwu E; Ndubuaku, Victor Chijioke; Ifeanyi, Ozioma Patricia (The Economics and Finance Letters, 2019)
This work was set out to measure the responsiveness of foreign reserves to exchange rate variables with a focus on the Nigerian economy. Foreign reserve was used as a dependent variable and all the exchange rate related variables used as independent variables. Time series data spanning 1996 to 2016 was used. A combined use of the Auto Regressive Distributed Lag Model (ARDL) and correlation matrix were employed. It was found that a positively significant relationship exists between real exchange rate and reserves with nominal exchange rate sharing a positive but non-significant relationship with foreign reserves. This makes a case for proper policy direction in the management of exchange rate in a manner that produces the best economic results for the Nigerian economy. The results are considered useful for economies in the shape of Nigeria for generalization and policy direction in the management of foreign reserve and its interface with exchange rate and its related factors.